2005
DOI: 10.1177/1045389x05055759
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, Optimization, and Design of Efficient Initially Curved Piezoceramic Unimorphs for Energy Harvesting Applications

Abstract: The piezoceramic, lead zirconate titanate (PZT), is capable of producing large voltages with relatively minimal currents in response to an applied mechanical load when employed in initially curved laminates. This study addresses the issue of optimizing design parameters of a curved PZT unimorph to maximize charge generation due to mechanical loading. A horizontally placed PZT unimorph structure generates surface charge when vertically loaded and the charge can be collected using charge-collecting circuitry. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 18 publications
(28 reference statements)
0
48
0
Order By: Relevance
“…Simply supported curved piezoelectric unimorphs similar to that shown in figure 5 have been modelled in more detail by Yoon et al [47]. The basic rules of thumb identified by the modelling suggested that it is more effective to increase the width of the unimorph rather than the length and that the height at the centre and the thickness of the substrate material should be maximized within the capability of the manufacturing process and the available compressing force.…”
Section: Human Powered Piezoelectric Generationmentioning
confidence: 99%
“…Simply supported curved piezoelectric unimorphs similar to that shown in figure 5 have been modelled in more detail by Yoon et al [47]. The basic rules of thumb identified by the modelling suggested that it is more effective to increase the width of the unimorph rather than the length and that the height at the centre and the thickness of the substrate material should be maximized within the capability of the manufacturing process and the available compressing force.…”
Section: Human Powered Piezoelectric Generationmentioning
confidence: 99%
“…A number of variations on this type of structure have been investigated. Several authors [54,62,63] have investigated the use of initially curved, or "pre-stressed" beams which have been demonstrated to give significantly higher output power than nonprestressed versions. A further development of this concept by Baker et al [57] involved the use of a curved beam between two pinned joints which could snap between concave and convex curves in response to excitation.…”
Section: Piezoelectric Conversionmentioning
confidence: 99%
“…Experimental results for this proposed method are not presented but it is apparent that ensuring efficient coupling between low and high frequency oscillators is critical to the efficiency of the overall structure. A fuller discussion of recent developments in piezo based devices is presented in [54].…”
Section: Piezoelectric Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…By considering an electric field equal to 0 and due to the fact that the PVDF films are only metalized in the plane perpendicular to direction 3, the charge developed on the surface of the PVDF, Q can be expressed as the integral of electrical displacement over the effective surface area of the electrodes on the material [8]:…”
Section: Piezoelectricitymentioning
confidence: 99%